2001
DOI: 10.1074/jbc.c100349200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus RNA-dependent RNA Polymerase (NS5B) as a Mediator of the Antiviral Activity of Ribavirin

Abstract: Ribavirin is administered in combination with interferon-␣ for treatment of hepatitis C virus (HCV) infection. Recently, we demonstrated that the antiviral activity of ribavirin can result from the ability of a viral RNA polymerase to utilize ribavirin triphosphate and to incorporate this nucleotide with reduced specificity, thereby mutagenizing the genome and decreasing the yield of infectious virus (Crotty, S., Maag, D., Arnold, J. J., Zhong, W., Lau, J. Y., Hong, Z., Andino, R., and Cameron, C. E. (2000) Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
201
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(213 citation statements)
references
References 15 publications
(19 reference statements)
9
201
3
Order By: Relevance
“…Recently, Cameron and colleagues (21,22) showed that ribavirin can be misincorporated into mRNA by viral RNA-dependent RNA polymerases because of its chemical similarity to guanosine, and this outcome leads to lethal mutagenesis of genomes of polio and HCV. Ribavirin triphosphate (RTP) binds the HCV polymerase with an observed dissociation constant (K d ) of 0.58 mM (23), which is consistent with micromolar concentrations necessary to achieve a therapeutic effect against HCV clinically (24). In addition to effects at millimolar concentrations, ribavirin is also active at micromolar concentrations.…”
mentioning
confidence: 80%
“…Recently, Cameron and colleagues (21,22) showed that ribavirin can be misincorporated into mRNA by viral RNA-dependent RNA polymerases because of its chemical similarity to guanosine, and this outcome leads to lethal mutagenesis of genomes of polio and HCV. Ribavirin triphosphate (RTP) binds the HCV polymerase with an observed dissociation constant (K d ) of 0.58 mM (23), which is consistent with micromolar concentrations necessary to achieve a therapeutic effect against HCV clinically (24). In addition to effects at millimolar concentrations, ribavirin is also active at micromolar concentrations.…”
mentioning
confidence: 80%
“…It is probable that this situation will extend to other RdRPs, especially the enzyme from hepatitis C virus (47). Therefore, it is reasonable to target the elongation complex for antiviral drug development.…”
Section: Implications For Development Of Antiviralsmentioning
confidence: 99%
“…[66][67][68][69] It is well absorbed from the proximal gut and has a large apparent volume of distribution because of its rapid entry into all cell types, which is mediated by small es-nucleoside transporters. It is not bound to plasma proteins and is eliminated slowly from intracellular and extracellular compartments.…”
Section: Ifn-␣mentioning
confidence: 99%
“…66,68,69 Polarization of a T H 1 response would be expected to enhance both cytokine-and CTL-mediated clearance of HCV-in- …”
Section: Ifn-␣mentioning
confidence: 99%